Short article: Presence, extent and location of pancreatic necrosis are independent of aetiology in acute pancreatitis. Issue 3 (March 2018) - Verdonk, Robert C.; Sternby, Hanna; Dimova, Alexandra; Ignatavicius, Povilas; Koiva, Peter; Penttila, Anne K.; Ilzarbe, Lucas; Regner, Sara; Rosendahl, Jonas; Bollen, Thomas L.
Abstract : Objective: The most common aetiologies of acute pancreatitis (AP) are gallstones, alcohol and idiopathic. The impact of the aetiology of AP on the extent and morphology of pancreatic and extrapancreatic necrosis (EXPN) has not been clearly established. The aim of the present study was to assess the influence of aetiology on the presence and location of pancreatic necrosis in patients with AP. Patients and methods: We carried out a post-hoc analysis of a previously established multicentre cohort of patients with AP in whom a computed tomography was available for review. Clinical data were obtained from the medical records. All computed tomographies were revised by the same expert radiologist. The impact of aetiology on pancreatic and EXPN was calculated. Results: In total, 159 patients with necrotizing pancreatitis were identified from a cohort of 285 patients. The most frequent aetiologies were biliary (105 patients, 37%), followed by alcohol (102 patients, 36%) and other aetiologies including idiopathic (78 patients, 27%). No relationship was found between the aetiology and the presence of pancreatic necrosis, EXPN, location of pancreatic necrosis or presence of collections. Conclusion: We found no association between the aetiology of AP and the presence, extent and anatomical location of pancreatic necrosis.